Enhancing Measuring Reliability: Calibration and Validation of IoT-based DC Power Logger - Arifa, Aulia; Suharno, Suharno; Kamaruddin, Maqbul; Harjunowibowo, Dewanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
A power logger is a device that has an electrical energy consumption monitoring function with an embedded data storage system to understand energy consumption patterns and improve the efficiency of energy usage. However, building meters without calibration causes inaccurate measurements and information. Therefore, the study reports a simple method to enhance any system's measurement quality via an Internet of Things (IoT)-based DC Power Logger case. The IoT system built in the Blynk application enables the power logger to operate remotely and was integrated into a Google spreadsheet page to facilitate real-time data storage with an INA219 sensor as the measurement module. The calibration process of the power logger was conducted by comparing the measurement results obtained from the power logger with measurements obtained from a Sanwa multimeter. As a result, the calibration process ensures enhanced accuracy and precision of power logger measurements, which was validated by the validation process.